PENEMPATAN PEGAWAI DALAM MENINGKATKAN KINERJA DI LINGKUNGAN KERJA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KOTA SAMARINDA - Isra Yuliana; Djumadi .; Dan Buntu Paranoan (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The aim of this study is to describe and analyze the placement of officers in improving their performance. The data are taken from the informants and key informants then supported by secondary data. In analyzing the data, this study uses interactive model developed by Miles and Huberman.